2019
DOI: 10.1177/1367877919859898
|View full text |Cite
|
Sign up to set email alerts
|

The aesthetics of dissent: Culture and politics of transformation in the Arab world

Abstract: Our special issue captures the interplay of media, politics, religion, and culture in shaping Arabs’ search for more stable governing models at a crossroads of global, regional, and national challenges through systematic and integrated analyses of evolving and contested Arab visual and performing arts in revolutionary and unstable public spheres. The issue presents a unique attempt to investigate these forms of cultural production as new modes of knowledge that shed light on the nature of social movements with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The Arab media further plays a crucial role in enhancing strategic economic partnerships in the region. According to Mohamed et al (2020), the press plays the essential role of providing public and government linkages that remains essential for economic development. Any government has to ensure that they promote the best interest of the citizens through the construction of an actionable economic agenda.…”
Section: A Literature Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The Arab media further plays a crucial role in enhancing strategic economic partnerships in the region. According to Mohamed et al (2020), the press plays the essential role of providing public and government linkages that remains essential for economic development. Any government has to ensure that they promote the best interest of the citizens through the construction of an actionable economic agenda.…”
Section: A Literature Analysismentioning
confidence: 99%
“…According toAhmed and Cho (2019), most countries hold that education is one of the critical pillars to economic prosperity. Education is a crucial cornerstone for the region's economic, political, and social capital within Arabian counties Mohamed et al (2020). noted the Arabian government's commitment to promoting sustainable economic development through collaboration with media houses.…”
mentioning
confidence: 99%
“…In the aftermath of the uprisings, Biagini (2020: 399) found that a generation of young women who participated in the 'revolutionary struggle and the subsequent repression of Islamists fostered the development of a gendered awareness that has resulted in these women's adoption of a new gender politics' with 'feminist overtones'. The uprisings created a climate in which less-traditional forms of self-expression (i.e., street art, rap) developed and reached new audiences through the use of social media (Mohamed, Mahdi and Dabashi, 2020). In particular, Walsh (2017: n.p.)…”
Section: Background To the Study: The Cairollers And Roller Derby In mentioning
confidence: 99%
“…The uprisings created a climate in which less traditional forms of self-expression (i.e. street art, rap) developed and reached new audiences through the use of social media (Mohamed et al, 2020). In particular, Walsh (2017: n.p.)…”
Section: Background To the Study: The Cairollers And Roller Derby In Egyptmentioning
confidence: 99%
“…Scholars have covered such media extensively in Arab sociopolitics, whether in Arab Spring revolutionary spheres during 2011 as in Egypt, Syria, Tunisia, and Yemen, or 2019 as in Algeria and Sudan. 1 Little has been written about the dynamics of such media MENA Migrants and Diasporas in Twenty-First-Century Media 3 productions in nonrevolutionary contexts, especially one that deals with immigrant labor in the Gulf Cooperation Council (GCC). Additionally, the essay accentuates the importance of the "cultural" in addition to the economic, social, and political layers that have received much of the attention of contemporary scholarship examining South Asian labor in the GCC.…”
mentioning
confidence: 99%